Effects of enzymes originating from Trichoderma reesei on the performance, organ index, serum biochemical indices, and intestinal health homeostasis of broiler chicken - Zhang, Luyao; Liu, Yang; Xie, Chunyuan; Huang, Xuan; Deng, Ping; Li, Chuang; Wan, Weican; Dai, Qiuzhong; Hu, Yan; Ma, Yuyong; Zhang, Xu; Jiang, Guitao (Frontiers in Veterinary Science, 2025)
To study the effect of combined enzymes from Trichoderma reesei on growth performance, organ index, serum biochemical indices, and gut microbiota in broiler chickens, an experiment was conducted with 648 one-day-old AA broilers. The broilers were randomly divided into six groups. The control group was fed a corn-soybean meal basal diet, and the experimental groups were supplemented with different enzyme combinations. The experiment lasted 42 d. The results showed that from day 1–21, the average daily gain (ADG) of T1–T4 groups was higher than that of the control group (P = 0.005). From day 22–42, T2 had a higher ADG than T3 and T4 (P = 0.017). T1, T3, and T4 had a lower feed-to-gain ratio (F/G) than the control group from day 1–21 (P = 0.001).In terms of serum indices, T1–T5 had higher levels of triiodothyronine (T3), growth hormone (GH), and insulin-like growth factor-1 (IGF-1) at 21 and 42 days compared to the control group (P < 0.001), with some exceptions. T2–T5 had higher levels of superoxide dismutase (SOD), glutathione peroxidase (GSH-PX), and glutathione (GSH) at 21 and 42 days (P < 0.001), with some exceptions. For organ indices, T3 had a lower gizzard index and T5 had a higher gizzard index than the control group (P = 0.001), and T4 had a lower liver index than the control group (P = 0.041). Enzyme supplementation also changed the gut microbiota.In conclusion, all enzyme systems improved broiler growth performance from day 1–21. Only xylanase and the carbohydrase system from Trichoderma reesei enhanced growth from day 22–42. All enzyme systems enhanced antioxidant and immune capacities during the study period.